Part I.: Friction stir welding of equiatomic nickel titanium shape memory alloy – microstructure, mechanical and corrosion behavior - Parker West (17268946) (2021)
In this study, friction stir welding (FSW) process is utilized to join equiatomic nickel-titanium (NiTi) shape memory alloys as a solid-state welding alternative to fusion welding. In the studied range of process parameters (spindle speeds – 350 – 450 rpm and constant translation speed 75 mm/min), combination of 400 rpm spindle speed and 75 mm/min tool translation speed produced a defect-free joint without any discernable voids. The weld microstructure consisted of a typical stir zone with fine grains; a rather small thermo-mechanically affected zone and heat affected zone. Vickers microhardness measurements after appropriate thermal cycling, showed uniform hardness across the weld zone, indicating a joint free of detrimental precipitates. The transformation temperatures measured by differential scanning calorimetry, showed little to no change across the weld zones. Under tensile loading, at ambient temperature a maximum joint efficiency of 93% was obtained in the martensitic phase while at elevated temperature a joint efficiency of 84% was obtained in the austenitic phase. The welded specimen showed martensitic detwinning plateau, characteristic of SMAs tested in martensitic phase, indicating that martensitic detwinning was the dominant mode of deformation at low strains, even within the weld zone. The weld zone showed comparatively lower corrosion resistance than the base material, owing to less dense TiO2 passive layer formation. Galvanic effect between the weld zone and base materials was negligible, indicating good compatibility between the different weld zones. Our results show that friction stir welding can be successfully applied for joining NiTi SMAs sheets. Other Information Published in: Journal of Advanced Joining Processes License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jajp.2021.100071